1991
DOI: 10.1177/002221949102400905
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Native Language Difficulties Among Foreign Language Learners in College: A "Foreign" Language Learning Disability?

Abstract: The present study compared successful and unsuccessful college foreign language learners on measures of intelligence, foreign language aptitude, native oral and written language, and math. Unsuccessful students had received petitions to waive the foreign language requirement. No significant differences between groups were found on intelligence and reading comprehension. Significant differences were found on the Modern Language Aptitude Test, on tests of written and oral language in the syntactic and phonologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
3
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 49 publications
7
78
3
3
Order By: Relevance
“…They were therefore excluded from the LISREL analysis. Further support for their exclusion came from previous L2/FL research studies that did not find semantic tasks in L1 to predict reading in L2/FL (Ganschow et al, 1991;Sparks & Ganschow, 1993a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were therefore excluded from the LISREL analysis. Further support for their exclusion came from previous L2/FL research studies that did not find semantic tasks in L1 to predict reading in L2/FL (Ganschow et al, 1991;Sparks & Ganschow, 1993a).…”
Section: Resultsmentioning
confidence: 99%
“…Sparks and Ganschow based the LCDH on L1 reading research conducted by Vellutino and Scanlon (1986), who found that poor L1 readers had difficulty with the structural aspects of the printed word, particularly with the phonological and orthographic aspects, but also with the syntactic aspects. In their research with high school and college students, Sparks and Ganschow found that these ''core'' linguistic abilities also affected FL learning (including reading) (Ganschow, Sparks, Javorsky, Pohlman, & Bishop-Marbury, 1991;Sparks & Ganschow, 1993a).…”
Section: Core Linguistic Abilities Underlying L1 and Fl Readingmentioning
confidence: 99%
“…In their research study on college students with foreign language learning difficulties, Ganschow et al (1991) formulated a theory, which attempts to explain the problems and variations in foreign language acquisition, the Foreign Language Linguistic Coding Differences Hypothesis (LCDH). This theory posits native language difficulties as the cause and predictor of foreign language difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, our participants were all college students. A review of the literature on the WRAT IV reading comprehension section reveals that this section has been used on college students with learning disabilities (Hughes & Smith, 1990) and nonnative speakers (Ganschow, Sparks, Javorshy, & Pohlman, 1991). This suggests that there is a possible ceiling effect of reading comprehension scores in a normal college population.…”
Section: Discussionmentioning
confidence: 99%